Factors influencing consumer purchasing behaviour of Christian gospel music in South Africa - Mosupye, Lebogang (My University, 2013)
Sales of Christian gospel music have decreased in the last decade, meaning that consumers have not being buying the music as often and as much as they used to. This study seeks to identify the factors influencing the purchasing behaviour of Christian gospel music consumers, with the focus being on motivation factors. The aim is to establish a marketing strategy for this specific consumer. The research employed a company to collect data around Johannesburg. Furthermore, the author collected more data at Rhema South Church as well as from colleagues via e-mail. Three music store managers were randomly chosen and interviewed to find out what their opinion was on the issue. Both quantitative and qualitative data was collected. It was found that Christian gospel music consumers are most motivated by Attribution and Stimulation. Therefore, the Christian gospel music consumer buys gospel music mainly to praise and worship God, to have communion and communication with Him, to be healed in their spirit when grieved and to be encouraged. It was also found that the marketing mix does further enhance the sales of gospel music, but only slightly. Piracy on the other hand, was found not to be a contributing factor to the decline of sales, as some might think. The key message is that the stakeholders (gospel music artists, suppliers of gospel music, music store managers and consumers) should all play a role in the increase of gospel music sales. Gospel music artists must become more creative and more original as this greatly affects consumer purchases, suppliers and distributors of gospel music must deliver the music to the consumer timeously and at the right price, and store managers must focus on promotion as a strategy to attract consumers to buy gospel music.
MBA thesis
Keywords: Music purchases; Gospel music; Christian gospel music